Capitalism, Coronavirus and War A Geopolitical Economy - Desai, Radhika (Rethinking Globalizations, 2023)
Capitalism, Coronavirus and War investigates the decay of neoliberal financialised capitalism as revealed in the crisis the novel coronavirus triggered but did not cause, a crisis that has been deepened by the conflict over Ukraine and its repercussions across the globe. Leading domestically to economic and political breakdown, the pandemic accelerated the decline of the US-led capitalist world's imperial power, intensifying the tendency to lash out with aggression and militarism, as seen in the US-led West's New Cold War against China and the proxy war against Russia over Ukraine. The geopolitical economy of the decay and crisis of this form of capitalism suggests that the struggle with socialism that has long shaped the fate of capitalism has reached a tipping point. The author argues that mainstream and even many progressive forces take capitalism's longevity for granted, misunderstand its historical dynamics and deny its formative bond with imperialism. Only a theoretically and historically accurate account of capitalism's dynamics and historical trajectory, which this book provides, can explain its current failures and predicament. It also reveals why, though the pandemic-by revealing capitalism's obscene inequality and shocking debility-prompted the most serious critiques of capitalism to emerge in decades, hopes of 'building back better' were so quickly dashed. This book sheds searching light on the dominant narratives that have normalised the neoliberal financialised capitalism and the dollar creditocracy dominating the world economy, with even critics unable to link capitalism's neoliberal turn to its financialisations, historical decay, productive debility and international decline. It contends that only by appreciating the seriousness of the crisis and rectifying our understanding of capitalism can progressive forces thwart a future of chaos and/or authoritarianism and begin the long task of building socialism. This book will be of great interest to students, scholars and researchers of international relations, international political economy, comparative politics and global political sociology.